Expression of Heparanase in Vasculature Cells and Astrocytes of the Mouse Brain after Focal Cerebral Ischemia - Li, Jimei (2011)
Heparanase is a heparan sulfate degrading endoglycosidase. Previous work has demonstrated that heparanase plays important roles in various biological processes including angiogenesis, wound healing and metastasis. However, the role of heparanase in the post-ischemic brain is not well defined. Transient focal cerebral ischemia in adult mice was induced by ligations of the right middle cerebral artery (MCA) and both common carotid arteries (CCAs). All mice were subjected to bromodeoxyuridine (BrdU) injection and sacrificed at different time points after stroke for immunohistochemical and Western blot analyses. Heparanase expression increased after ischemia in both cell-specific and time-dependent manners. Three to 7 days after stroke, levels of the 50-kD heparanase, basic fibroblast growth factor (FGF-2), and angiopoietin-2 (Ang-2) increased in the peri-infarct region. At early time points, heparanase expression was largely confined to proliferating vascular endothelial cells. At 14 days after ischemia, this expression had shifted to astrocytes in the same region. These data show that cerebral ischemia markedly increases heparanase levels in endothelial cells and then in astrocytes. The unique features of the heparanase upregulation imply that heparanase may play specific roles in the pathological and regenerative processes during the acute and sub-acute/chronic phase in the post-stroke brain.